The effect of low‐ and high‐velocity tendon excursion on the mechanical properties of human cadaver subsynovial connective tissue. Issue 1 (13th September 2013) - Filius, Anika; Thoreson, Andrew R.; Yang, Tai‐Hua; Vanhees, Matthias; An, Kai‐Nan; Zhao, Chunfeng; Amadio, Peter C.
SUMMARY Fibrosis of the subsynovial connective tissue (SSCT) in the carpal tunnel is the most common histological finding in carpal tunnel syndrome (CTS). Fibrosis may result from damaged SSCT. Previous studies found that with low‐velocity (2 mm/s), tendon excursions can irreversibly damage the SSCT. We investigated the effect of tendon excursion velocity in the generation of SSCT damage. Nine human cadaver wrists were used. Three repeated cycles of ramp‐stretch testing were performed simulating 40%, 60%, 90%, and 120% of the middle finger flexor tendon superficialis physiological excursion with an excursion velocity of 60 mm/s. Energy and force were calculated and normalized by values obtained in the first cycle for each excursion level. Data were compared with low‐velocity excursion data. For high‐velocity excursions, a significant drop in the excursion energy ratio was first observed at an excursion level of 60% physiological excursion (p < 0.024) and that for low‐velocity excursions was first observed at 90% physiological excursion (p < 0.038). Furthermore, the energy ratio was lower at 60% for high velocities (p ≤ 0.039). Increasing velocity lowers the SSCT damage threshold. This finding may be relevant for understanding the pathogenesis of SSCT fibrosis, such as that accompanying CTS, and a relationship with occupational factors. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:123–128, 2014.